Correlation Between Data Adjustment and Property Time on Market: Evidence from Jakarta Indonesia - Riyanto, Edy; Prasetyo, Kristian Agung (Jurnal Ilmu Manajemen dan Ekonomika, 2025)
Property valuation in emerging markets often relies on asking prices due to limited access to verified transaction data. This reliance requires a data-type adjustment to reduce the gap between asking and transaction prices. Meanwhile, literature suggests a potential relationship between price concessions and time on market (TOM). This study aims to examine whether listing duration is significantly correlated with the magnitude of data-type adjustment in Jakarta’s residential property market. Using 331 verified transaction data from the Directorate General of State Assets (DJKN), the research applies descriptive statistics, chi-square tests, and polychoric correlation analysis. The results show that although 67.7% of properties were sold within six months, no significant correlation was found between TOM and data-type adjustment (r = 0.08, p = 0.74). Instead, the role of intermediaries such as brokers and agents appeared to have greater influence on narrowing the gap between asking and transaction prices. The findings indicate that the price–duration trade-off commonly reported in developed markets does not apply in Jakarta. This study highlights the importance of empirical evidence in determining adjustment practices and provides practical implications for valuers, brokers, and policymakers in emerging markets.